The use of spacers (static and mobile) in infection knee arthroplasty - Mazzucchelli, Luca (Curr Rev Musculoskelet Med, 2015)
Revision total knee arthroplasty (TKA) is the treatment of choice in patients with periprosthetic joint infection. It may be performed in either a single stage or two stages. In the latter option, between stages, an antibiotic-loaded spacer may be used to maintain a certain amount of joint stability and mobility after the infected implant is removed, adding an intra-articular concentration of antibiotics. There are two types of antibiotic-loaded cement spacers: static and dynamic. Static spacers basically create a temporary arthrodesis with antibiotic-loaded cement and usually are handmade within the surgical field. Dynamic spacers can be created intraoperatively by using different tools or may be prepackaged by the manufacturer; they allow range of motion between stages. In this article, the authors review the indications, surgical techniques, and results for static and dynamic spacers in two-stage revision TKA.